Platelet-Platelet Recognition During Aggregation: Distinct Mechanisms Determined by the Release Reaction - Agam, Galila; Livne, Avinoam (Thrombosis and Haemostasis, 1984)
Fixed platelets, bearing covalently bound fibrinogen, were previously shown to participate passively in aggregation induced by thrombin or A23187. The bound fibrinogen was specifically required for the interaction. The present study examines the role of the release reaction in controlling the passive participation of the fixed platelets in aggregation. Aggregation of fresh platelets induced by low ADP concentration (≤2 μM) was not augmented by the fixed platelets, but was augmented when higher concentrations of ADP were employed. Fixed platelets failed to enhance aggregation of aspirin-treated fresh platelets induced by 10 μM ADP; the augmentation capability was reconstituted by a supernatant fraction from platelets activated by 10 μM ADP in the presence of EDTA. The binding of soluble fibrinogen to activated fresh platelets occurred regardless of the release reaction, but the interaction of fragmented fixed platelets bearing bound fibrinogen with aggregating fresh platelets was apparent only when release took place. It is concluded that fibrinogen covalently bound to fixed platelets is selectively recognized by released compound(s).
Keywords: Platelet recognition; Aggregation; ADP; Release reaction